2022
DOI: 10.1002/acn3.51508
|View full text |Cite
|
Sign up to set email alerts
|

Epidural stimulation with locomotor training ameliorates unstable blood pressure after tetraplegia. A case report

Abstract: A male with C7 complete tetraplegia participated in 14 weeks of body weight supported treadmill training (BWSTT) combined with spinal cord epidural stimulation (SCES), 4 weeks of no intervention, and two more weeks of BWSTT + SCES. The participant presented with unstable resting seated blood pressure (BP; 131/66 mmHg). After retrospective analysis, resting systolic BP decreased and diastolic BP increased, yielding a safe mean arterial BP. There was a fivefold increase in BWSTT bouts per session, and percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The novelty of this case report needs to be highlighted. We have utilized percutaneous SCES implantation and not paddle implantation as has been demonstrated with several other groups ( Aslan et al, 2018 ; Darrow et al, 2019 ; Ditterline et al, 2020 ; Squair, 2021 ; Gorgey et al, 2022 ). The point is not to emphasize the use of percutaneous leads over paddle implantation but to demonstrate the fact that there is an alternative approach that may yield positive results similar to the paddle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novelty of this case report needs to be highlighted. We have utilized percutaneous SCES implantation and not paddle implantation as has been demonstrated with several other groups ( Aslan et al, 2018 ; Darrow et al, 2019 ; Ditterline et al, 2020 ; Squair, 2021 ; Gorgey et al, 2022 ). The point is not to emphasize the use of percutaneous leads over paddle implantation but to demonstrate the fact that there is an alternative approach that may yield positive results similar to the paddle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mechanisms for regulating hemodynamic challenges after SCI has been recently highlighted in rodents, primates and humans with SCI ( Squair, 2021 ). We have recently shown that 14 weeks of body weight supported treadmill training with SCES, resulted in normalized unstable resting seated blood pressure, increased the number of training bouts per session, and decreased the percentage of body weight support to 69% ( Gorgey et al, 2022 ). The aforementioned studies focused primarily on studying paddle implantation with limited evidence about the feasibility of using implanted percutaneous SCES to enhance autonomic functions in persons with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…It has not been until recently that the applications of scES have emerged for the restoration of motor recovery in neurological disorders, especially in persons with spinal cord injury (SCI) [ 3 , 4 , 5 ]. We have previously used scES to enhance motor and autonomic functions in a person with complete SCI [ 6 , 7 ]. Unlike paddle implantation, percutaneous lead implantation provides access to the epidural space without the need to perform surgical laminectomy or laminotomy.…”
Section: Case Reportmentioning
confidence: 99%